THE COMMENCEMENT OF INTERNATIONAL ARMAMENT RACE DURING THE "COLD WAR" ERA (NATO AND THE WARSAW PACT'S MILITARY ACTIVITIES AS EXAMPLES) - Akromova Shoistakhon Jaloliddin qizi (American Journals Publishing, 2023)
In the second half of the 20th century, the political situation in the world was characterized by the emergence of rivalry between the two major powers, the United States and the former Soviet Union, known as the "Cold War" policy. After the Second World War, the division of global power into two spheres, with Europe and Asia aligning themselves with either of the two ideological systems, became evident. Under the leadership of the United States, the European economic cooperation organization was formed, followed by the establishment of the Western political organization, the North Atlantic Treaty Organization (NATO). The formation of the Western Atlantic bloc marked a division into two camps in the world. At that time, the issue of integration of Western European states was a significant concern in Washington.
Keywords: NATO, USSR, USA, Afghanistan, North Atlantic Treaty, Europe, North America,